PERAN DINAS PERHUBUNGAN DALAM PENGAWASAN TERHADAP PEMBUATAN ALAT PEMBATAS KECEPATAN DI KOTA BATAM - Siregar, indra Miharja; Arman, Zuhdi (LPPM Universitas Putera Batam, 2020)
Vehicle speed limiting one of the road safety embankments made so that the driver reduces the vehicle speed. Construction of rapid mounds is only in residential areas, local roads that have IIIC road classes, and roads that are being built. Some problems related to the role of the transportation department in overseeing the manufacture of speed tools in Batam City include the role of the Batam City Transportation Office in relation to supervision and the impact of traffic on making speed bumps. The purpose of this study is to describe the role of the Department of Transportation to oversee the manufacture of vehicle speed limiting devices in the city of Batam, and the impact of traffic on the creation of speed bumps that do not comply with Law Number 22 Year. 2009 on Road Traffic. The main sources of this research are surveys and interviews which are then reviewed by statutory provisions, with an empirical sociological approach. Data analysis uses empirical sociological analysis. Based on the results and discussion related to supervision and the impact of making a speed bump. Thus, inductive conclusions are drawn based on facts found in the field. Keywords: speed limits, vehicles, society